Magnetoresistive emulsion analyzer - Lin, Gungun; Baraban, Larysa; Han, Luyang; Karnaushenko, Daniil; Makarov, Denys; Cuniberti, Gianaurelio (Giovanni); Schmidt, Oliver G. (Scientific Reports, 2013)
We realize a magnetoresistive emulsion analyzer capable of detection, multiparametric analysis and sorting of ferrofluid-containing nanoliter-droplets. The operation of the device in a cytometric mode provides high throughput and quantitative information about the dimensions and magnetic content of the emulsion. Our method offers important complementarity to conventional optical approaches involving ferrofluids, and paves the way to the development of novel compact tools for diagnostics and nanomedicine including drug design and screening.
CRIS-Team Scopus Importer:2023-03-20